Analytical Competences of Teachers in Big Data in the Era of Digitalized Learning - Jesús López-Belmonte; Santiago Pozo-Sánchez; Arturo Fuentes-Cabrera; Juan-Manuel Tr (MDPI AG, 2019)
The progress of technology in the field of education has led to the development of new professional skills in the teaching community, such as digital competence. Likewise, it has propagated the appearance of new learning environments mediated by technological resources that favor the generation of a large volume of data, known as Big Data, derived from the interactions of educational agents in virtual environments. This study aims to determine the level of digital competence in the informational area of teachers and to determine the projection of Big Data in them. For this study, a descriptive and correlational quantitative method was followed. The study sample consists of 832 Spanish teachers, with data collected through a questionnaire. The results reveal that the teaching staff have a medium level of digital competence in the informational area. The teachers obtained better valuations in the dimensions concerning storage and recovery, postulating themselves as connoisseurs of the Big Data concept to a large extent. In some instances, the teachers affirmed that sometimes they access and interpret the data generated by the digital interactions, transforming it into useful information to improve their teaching processes. Finally, our research shows that the level of digital competence in the informational area influences the degree of knowledge about Big Data.